2008
DOI: 10.1038/nm1730
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular nitric oxide gradients normalize tumor vasculature

Abstract: Normalization of tumor vasculature is an emerging strategy to improve cytotoxic therapies. Here we show that eliminating nitric oxide (NO) production from tumor cells via neuronal NO synthase silencing or inhibition establishes perivascular gradients of NO in human glioma xenografts in mice and normalizes the tumor vasculature, resulting in improved tumor oxygenation and response to radiation treatment. Creation of perivascular NO gradients may be an effective strategy for normalizing abnormal vasculature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 13 publications
6
108
0
2
Order By: Relevance
“…to total amount, are critical to its ultimate function (16,29). Under physiological conditions, eNOS produces NO in lymphatic endothelial cells at specific locations and times during a contraction cycle (22), which facilitates diastolic filling.…”
Section: Discussionmentioning
confidence: 99%
“…to total amount, are critical to its ultimate function (16,29). Under physiological conditions, eNOS produces NO in lymphatic endothelial cells at specific locations and times during a contraction cycle (22), which facilitates diastolic filling.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed below, many studies testing the effects of antiangiogenic drugs have shown a presence of a "normalization window"-a time period beginning with the appearance of a normalized vascular phenotype (typically within 1 -2 days of starting treatment), and ending when features of normalization are lost Winkler et al 2004;Jain 2005b;Batchelor et al 2007;Kamoun et al 2009 Xian et al 2006;McCarty et al 2007;Mazzone et al 2009. c This is controversial given recent reports of increased metastasis after antiangiogenic therapy in certain animal models (Ebos et al 2009;Paez-Ribes et al 2009 Gorski et al 1999;Hansen-Algenstaedt et al 2000;Lee et al 2000;Kozin et al 2001;Ader et al 2003;Winkler et al 2004;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006a;Dings et al 2007;Kashiwagi et al 2008;Batra et al 2009;Cerniglia et al 2009;Tsukada et al 2009;McGee et al 2010. g Teicher et al 1995a,b;Wildiers et al 2003;Segers et al 2006;Dickson et al 2007a,b,c;Bhattacharya et al 2008Bhattacharya et al , 2009Zhou et al 2008;Juan et al 2009;Zhou and Gallo 2009;J Liu, S Liao, B Diop-Frimpong, et al, unpubl. data. section, we discuss the key molecules implicated in tumor vessel biology with a focus on their role in regulating vascular normalization.…”
Section: Evidence For Vascular Normalization In Tumors Preclinical Evmentioning
confidence: 99%
“…Lee et al 2000;Winkler et al 2004;Dings et al 2007;Fischer et al 2007;Eichhorn et al 2008;Batra et al 2009;Skuli et al 2009;McGee et al 2010. j Teicher et al 1995bJain et al 1998;Bernsen et al 1999;Cohen-Jonathan et al 2001;Delmas et al 2003;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006b;Segers et al 2006;Cerniglia et al 2009;Qayum et al 2009;Cham et al 2010. k Ader et al 2003;Hamzah et al 2008;Kashiwagi et al 2008;Stockmann et al 2008;Maione et al 2009;Mazzone et al 2009;Skuli et al 2009;Tsukada et al 2009;Rolny et al 2011. l Yuan et al 1996Lee et al 2000;Wildiers et al 2003;Tong et al 2004;Nakahara et al 2006;Dickson et al 2007b;Kurozumi et al 2007;Taguchi et al 2008;Zhou et al 2008;Kamoun et al 2009;Ohta et al 2009;Gallo 2009. m Jain et al 1998;Izumi et al 2002;…”
Section: Vegfunclassified
See 2 more Smart Citations